Incomplete Financial Contracts and Non-contractual Legal Rules: The Case of Debt Capacity and Fraudulent Conveyance Law - Heaton, J.B. (Journal of Financial Intermediation, 2000)
This paper illustrates how non-contractual legal rules sometimes alleviate contractual incompleteness. A serious incompleteness in debt contracts is the borrower's ability to fraudulently transfer assets to third parties, rendering the borrower insolvent. The incompleteness arises because contractual remedies are ineffective against third-party transferees who are not bound by the debt contract, while the borrower has no assets to recover. Fraudulent conveyance law is a non-contractual legal rule allowing recovery against these transferees. This increases debt capacity most dramatically for borrowers with highly liquid assets. Without non-contractual legal rules, high liquidation value implies low debt capacity. Journal of Economic Literature Classification Numbers: G32; G38.